Evaluation and characterization of intestinal oedema in pigs - Ortiz, A. L. (2012)
Introduction When characterizing small intestine early lesions in studies concerning intestinal hypoperfusion in pigs, authors faced a significant difficulty when trying to standard the oedema grading to allow an accurate comparison between groups. Therefore, specific alterations were assumed to characterize grade1 (G1), grade2 (G2) and grade3 (G3) oedema. Material and Methods Eighteen Large White pigs underwent total intravenous anaesthesia (TIVA) with propofol and remifentanil. 25 ml/kg of arterial blood were removed from the femoral artery over 20 minutes. Volume was replaced using Ringer Lactate in Gr1 (n=6) and Hydroxyethyl starch 130/0.4 in Gr2 (n=6), 20 minutes after bleeding. Animals of G3 (n=6) were under TIVA without any haemorrhage and volume replacement. One hour after, pigs were euthanized and small intestine samples taken for histopathological examination. Oedema was described and classified in a specific scale: G0-Normal–normal central lacteal G1-Mild–lacteal dilation G2-Moderate-lacteal dilation and/or oedema of lamina propria G3-Marked–lacteal dilation dilation, oedema of lamina propria, and/or presence of submucosal oedema Pictures were made to better characterize the scale used. Results G2 oedema was predominant in duodenum in Gr1 (n=3), while in Gr2 and Gr3 was G1 for the same intestinal segment (n=5, n=4, respectively). G1 was predominant in jejunum in Gr1 (n=4), while G2 and G0 was more observed in Gr2 (n=2, n=2, respectively) and G2 in Gr3 (n=3). G1 was predominant in ileum in both Gr1 (n=5) and Gr2 (n=4), being G0 the grade more often observed in this segment in Gr3 (n=3). Jejunum was the only intestinal segment were G3 oedema was observed, and only in Gr2 (n=1).The higher frequency of G0 oedema for all the intestinal segments was observed in Gr3 (n=8). Conclusion The characterization used for the different grades of oedema improved uniformity when deciding which grade to attribute in each case and may allow standardization of oedema grading in further studies.